Antenatal Schools – Benefits and Attitudes - Gencheva, Hristina (Türkiye Sağlık Okuryazarlığı Dergisi, 2026)
Antenatal schools are structured educational programs aimed at supporting expectant mothers and their partners during pregnancy, childbirth, and providing early newborn care.Objective: This study aims to explore the opinions and attitudes of expectant parents regarding participation in antenatal school programs.Materials and Methods: A cross-sectional study was conducted using a combination of sociological and statistical methods. Data were collected through an online survey administered to pregnant women and expectant parents. Descriptive statistical analysis was applied to evaluate participants’ attitudes toward antenatal school attendance and perceived benefits.Results: Antenatal schools currently reach a considerable proportion of pregnant women; however, the findings indicate potential for broader participation. Pregnant women and mothers-to-be demonstrate a high level of awareness regarding the importance and usefulness of antenatal education, whereas their partners show comparatively lower engagement. The majority of respondents identify antenatal school participation as beneficial, particularly in relation to preparation for childbirth and newborn care.Conclusion: Antenatal schools play a significant role in preparing expectant mothers for childbirth and in developing practical skills for newborn care. Midwives have a central supportive role in antenatal education and contribute substantially to improving maternal knowledge and confidence.